Concurrent Occurrence of Tumor in Colon and Small Bowel following Intestinal Obstruction: A Case Report and Review of the Literature - Seyed Mohammad Reza Nejatollahi; Omid Etemad (Case Reports in Surgery)
An intestinal obstruction occurs when either the small or large intestine is partly or completely blocked so it prevents passing the food or fluid through the small/large bowel. This blockage is due to the existence of a mechanical obstruction such as foreign material, mass, hernia, or volvulus. Common symptoms include cramping pain, nausea and vomiting, changes in bowel habits, inability to pass stool, and lack of gas. We present a case of an 83-year-old man who had been referred to Taleghani Hospital with symptoms of bowel obstruction. He underwent the surgery. The findings of exploration of the entire abdomen showed two types of mass separately in two different organs. In postoperative workup, pathology reported two types of tumors (adenocarcinoma and neuroendocrine tumors).